2014
DOI: 10.1038/nature13162
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of entorhinal–hippocampal ensemble activity during associative learning

Abstract: 2Neural activity was recorded from EC and CA1 of 17 rats trained to solve a simplified version of an odour-place association task thought to depend on interfacing of the hippocampus with inputs from the olfactory bulb and the piriform cortex via the EC 13-15 ( Fig. 1; Supplementary Video 1). On each trial, the animal sampled odours in a cue port for 1 s and then, depending on odour identity, ran to either of two cups for food reward (Fig. 1b). Following 3 weeks of training, the percentage of correct trials inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
378
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 365 publications
(446 citation statements)
references
References 43 publications
39
378
3
1
Order By: Relevance
“…Converging evidence has suggested that hippocampal neurons respond also to nonspatial features of the environment, such as odors (Eichenbaum et al 1987;Wood et al 1999;Igarashi et al 2014), tactile inputs (Young et al 1994), and timing (Hampson et al 1993). The same cells that respond to nonspatial stimuli fire like place cells when animals move around in space, suggesting that place cells express the location of the animal in combination with information about events that take place or took place there (Leutgeb et al 2005b;Moser et al 2008).…”
Section: Place Cells Synaptic Plasticity and Memorymentioning
confidence: 99%
See 3 more Smart Citations
“…Converging evidence has suggested that hippocampal neurons respond also to nonspatial features of the environment, such as odors (Eichenbaum et al 1987;Wood et al 1999;Igarashi et al 2014), tactile inputs (Young et al 1994), and timing (Hampson et al 1993). The same cells that respond to nonspatial stimuli fire like place cells when animals move around in space, suggesting that place cells express the location of the animal in combination with information about events that take place or took place there (Leutgeb et al 2005b;Moser et al 2008).…”
Section: Place Cells Synaptic Plasticity and Memorymentioning
confidence: 99%
“…Recently, Igarashi et al (2014) recorded simultaneously from the lateral entorhinal cortex and CA1 region of the rat hippocampus as the animals learned an odor-place association. As the animals learned the association, the two structures showed an increasing degree of synchronous oscillatory activity in the 20-to 40-Hz range and a corresponding increase in spiking activity to the rewarded odors.…”
Section: Memory Encodingmentioning
confidence: 99%
See 2 more Smart Citations
“…Gamma oscillations provide a mechanism for dynamic coupling of selected cell assemblies 171,172 . Place cells in CA1 use fast gamma oscillations to couple to spatially modulated cell assemblies in MEC 173 whereas low-frequency betagamma oscillations enable coupling with odour-coding neurons in the lateral part of entorhinal cortex 174 . Because beta and gamma epochs are both short-lasting and regionally specific 173,174 , place cells may interact dynamically with a range of entorhinal cell assemblies each carrying a distinct type of information.…”
Section: Grid Cells and The Formation Of Place Fieldsmentioning
confidence: 99%